Letter to Jane Tolmach from Raoul Teilhet, President of California Federation of Teachers - Raoul Teilhet:::::: (1976)
In a June 11, 1976 letter, Raoul Teilhet, President of the California Federation of Teachers (AFT, AFL-CIO), congratulated Jane Tolmach on winning the Democratic nomination in the 36th Assembly District. He acknowledged the challenges ahead in the general election and assured her of the union's continued support. The letter conveyed both organizational backing and personal best wishes.